Chapter Appendice. Bruno Trentin e il dibattito costituzionale europeo - Supiot, Alain (Studi e saggi, 2021)
In the context of an article published in2005on foreign readings on the evolution of social law, the distinguished French scholar Alain Supiot connects the elaboration of The Freedom Comes First to the European constitutional debate of the 2000s. Trentin's reflections on the inseparable link between work and knowledge in the third industrial revolution and on the centrality of the person for a political reform project based on the revival of the European social model and on the role of a federal Europe in the governance of globalization are adequately underlined. The transnational dimension of Bruno Trentin's political thought is confirmed in the field of labour law and in the debate on the European social model and the future of Europe